TIM-3/Gal-9 interaction affects glucose and lipid metabolism in acute myeloid leukemia cell lines - Rezaei, Mahnaz; Ghanadian, Mustafa; Ghezelbash, Behrooz; Shokouhi, Abolfazl; Bazhin, Alexandr V.; Zamyatnin, Andrey A.; Ganjalikhani-Hakemi, Mazdak (Frontiers in Immunology, 2023)
Introduction T-cell immunoglobulin and mucin domain-3 (TIM-3) is a transmembrane molecule first identified as an immunoregulator. This molecule is also expressed on leukemic cells in acute myeloid leukemia and master cell survival and proliferation. In this study, we aimed to explore the effect of TIM-3 interaction with its ligand galectin-9 (Gal-9) on glucose and lipid metabolism in AML cell lines. Methods HL-60 and THP-1 cell lines, representing M3 and M5 AML subtypes, respectively, were cultured under appropriate conditions. The expression of TIM-3 on the cell surface was ascertained by flow cytometric assay. We used real-time PCR to examine the mRNA expression of GLUT-1, HK-2, PFKFB-3, G6PD, ACC-1, ATGL, and CPT-1A; colorimetric assays to measure the concentration of glucose, lactate, GSH, and the enzymatic activity of G6PD; MTT assay to determine cellular proliferation; and gas chromatography–mass spectrometry (GC-MS) to designate FFAs. Results We observed the significant upregulated expression of GLUT-1, HK-2, PFKFB-3, ACC-1, CPT-1A, and G6PD and the enzymatic activity of G6PD in a time-dependent manner in the presence of Gal-9 compared to the PMA and control groups in both HL-60 and THP-1 cell lines (p > 0.05). Moreover, the elevation of extracellular free fatty acids, glucose consumption, lactate release, the concentration of cellular glutathione (GSH) and cell proliferation were significantly higher in the presence of Gal-9 compared to the PMA and control groups in both cell lines (p < 0.05). Conclusion TIM-3/Gal-9 ligation on AML cell lines results in aerobic glycolysis and altered lipid metabolism and also protects cells from oxidative stress, all in favor of leukemic cell survival and proliferation.